Environmental Management and Sanitation as a Malaria Vector Control Strategy: A Qualitative Cross-Sectional Study Among Stakeholders, Sunyani Municipality, Ghana - Samuel Yaw Agyemang-Badu; Esi Awuah; Sampson Oduro-Kwarteng; Justice Yao Woelinam Dzamesi; Nazri Che Dom; Girum Gebremeskel Kanno (SAGE Publishing, 2023)
Background: For centuries malaria infection remains a public health burden globally as well as in the Sunyani Municipality. This exploratory qualitative study aimed to assess the prospects of environmental management and sanitation (EMS) as a malaria vector control strategy among key stakeholders involved in the prevention and control of malaria in Sunyani Municipality, Ghana. Method: We used an exploratory qualitative study and a designed focus group discussion (FGD) guide (with specific research questions) to solicit opinions and/or views among Malaria Control Focal Persons, Environmental Health Officers (Health Inspectors), and Honourable Assembly Members. Data were collected between December 2019 and February 2020. The responses were analyzed according to the specific research questions. Result: Findings from this study shows that high government support and/or political will by investing in environmental sanitation infrastructure, creating the enabling environment for strict enforcement of environmental sanitation bye-laws by Environmental Health Officers/Health Inspectors, effective and efficient collaboration among key stakeholders and organization of communal labor activities is likely to help reduce the majority of the mosquito breeding sites. Conclusion: The prospects of environmental management and sanitation (EMS) as a vector control strategy, look promisingly very high, pertinent, and workable and a likelihood game changer of winning the fight against malaria due to the residual transmission that is happening outdoors. However, EMS can be employed as a supplementary method to the current core vector control methods if the following conditions and bottlenecks are addressed and in place: (a) Effective collaboration among key stakeholders at all levels; (b) Adequate allocation of funds to the Environmental Health and Sanitation Department; (c) Enactment of robust educational campaigns across all educational levels and via different media; (d) Recognition, empowerment, and adequate resourcing of Environmental Health Officers; (e) Adherence to the building regulations to prevent encroachment of natural wetlands; (f) Revision of fees/fines and prosecution of sanitary offenders; (g) Enactment of an Environmental Sanitation Day (ESD), and establishment of the Environmental Health and Sanitation Fund (EHSF).